Policy and administration of the educational system in Spain: From the Ministry of Public Instruction to the Departments of Education of the Autonomous State - Ramírez Aísa, Elías (Historia y Memoria de la Educación, 2024)
Reseña del libro publicado por Jaime Antonio Foces Gil, editado por la Universidad de Valladolid.